The Yazidi Genocide in the Court of Frankfurt an Analytical Legal Study on The Case of Taha Al-Jumaili - Ahmed, Awara Hussein (As-Siyasi: Journal of Constitutional Law, 2023)
The Yazidis are one of the oldest ethnic and religious communities originating from the Middle East. The majority of Yazidis reside in northwestern Iraq, in the areas around Mount Shingal and the Shekhan district. Throughout their history, Yazidis have faced genocide and many international crimes, most notably the 2014 Genocide by the Islamic State in Iraq and Syria (hereafter referred to as ISIS or IS), which had a significant international impact. The United Nations has recognised these atrocities as genocide in several of its reports. Moreover, several ISIS perpetrators have been prosecuted in various states. However, the verdict of the Frankfurt regional high court in Germany (hereinafter referred to as the Frankfurt Court) to sentence Taha Al-Jumaili is considered the first decision acknowledging crimes against Yazidis as genocide based on absolute universal jurisdiction and, from a legal perspective, as a result of intensive efforts. This research aims to conduct a clear legal evaluation of the Frankfurt court's decision to sentence Taha Al-Jumaili and compare it with internationally recognised criminal law standards. The method used is a legal analysis method to examine the relevant international conventions, laws, and court rules. The research findings indicate that the aforementioned decision has a valuable legal basis, as the Frankfurt Court, in its decision, concluded that Genocide can be committed by killing just one person if the legal conditions of Genocide exist in the crime, which they did in the case of Taha Al-Jumaili. In this sense, a genocide crime can be committed by killing a single person. Taha Al-Jumaili's criminal liability was the murder of a Yazidi girl, and he received a life sentence as a Genocide criminal. This sentence is in line with internationally recognised criminal law standards.